Poly(A)-specific ribonuclease is a nuclear ribosome biogenesis factor involved in human 18S rRNA maturation. Issue 11 (10th April 2017) - Montellese, Christian; Montel-Lehry, Nathalie; Henras, Anthony K.; Kutay, Ulrike; Gleizes, Pierre-Emmanuel; O'Donohue, Marie-Françoise
Abstract: The poly-A specific ribonuclease (PARN), initially characterized for its role in mRNA catabolism, supports the processing of different types of non-coding RNAs including telomerase RNA. Mutations in PARN are linked to dyskeratosis congenita and pulmonary fibrosis. Here, we show that PARN is part of the enzymatic machinery that matures the human 18S ribosomal RNA (rRNA). Consistent with its nucleolar steady-state localization, PARN is required for 40S ribosomal subunit production and co-purifies with 40S subunit precursors. Depletion of PARN or expression of a catalytically-compromised PARN mutant results in accumulation of 3΄ extended 18S rRNA precursors. Analysis of these processing intermediates reveals a defect in 3΄ to 5΄ trimming of the internal transcribed spacer 1 (ITS1) region, subsequent to endonucleolytic cleavage at site E. Consistent with a function of PARN in exonucleolytic trimming of 18S-E pre-rRNA, recombinant PARN can process the corresponding ITS1 RNA fragment in vitro . Trimming of 18S-E pre-rRNA by PARN occurs in the nucleus, upstream of the final endonucleolytic cleavage by the endonuclease NOB1 in the cytoplasm. These results identify PARN as a new component of the ribosome biogenesis machinery in human cells. Defects in ribosome biogenesis could therefore underlie the pathologies linked to mutations in PARN.